ANALISIS PERENCANAAN KAWASAN PARIWISATA DANAU BUATAN KOTA PEKANBARU - Putra Agung Ramadhani; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The aim of this study was to see how Tourism Region planning Buatan Lake Pekanbaru. Tourism Regional Planning aims to increase the potential of existing attractions and Increase PAD Pekanbaru.This study used a qualitative research method with descriptive data analysis. The concept of using the theory of management theory and the concept of tourism planning. In collecting the data, the researcher used interview, observation, and documentation. By using key informants as a source of information and triangulation techniques as a source interview of data validation.These results indicate that the Planning Buatan Lake Pekanbaru tourism must be optimized to the maximum. The potential that exists in Buatan Lake very diverse and if developed would be the leading tourist sector as Sumatra. Additionally RIPPDA Pekanbaru City policy should be made as soon as possible, because the RIPPDA a guide line for the city of Pekanbaru in developing tourism. Especially Buatan Lake who became the leading tourism destinations Pekanbaru.Keywords:Planning, Attractions, PAD, Tourism Development Master Plan